Examination of the complex relationships among dietary components, type II diabetes, weight change, and breast cancer risk among Singaporean Chinese women - Canales, Lorena Lea, author; Peel, Jennifer, advisor; Clark, Maggie, committee member; Bachand, Annette, committee member; Nelson, Tracy, committee member; Ryan, Elizabeth, committee member (Colorado State University. Libraries, 2015)
Type II diabetes and breast cancer are on the rise in Asian populations that have typically had lower burdens of disease. Intake of dietary components high in nutrients with anti-oxidative and anti-inflammatory properties, such as green tea, soy, fruits and vegetables, may protect against the development of type II diabetes and may improve HbA1c (glycated hemoglobin) levels, a clinically relevant biomarker of diabetes and prediabetes. Furthermore, modifiable lifestyle factors such as diabetes, weight change and diet that influence endogenous hormone levels and the insulin pathway may play a role in the development of breast cancer. This dissertation includes three aims that examined different aspects of the complex relationships between diet, diabetes, weight change, and breast cancer risk in the Singapore Chinese Health Study, a prospective cohort study that enrolled 63,257 Chinese men and women aged 45-74 years between 1993 and 1998. First, we examined the association between intake of green tea, soy, and a vegetable-fruit-soy dietary pattern on HbA1c levels among self-reported, nondiabetic men and women, examined separately (Aim 1). We also evaluated type II diabetes and weight change (separately) in relation to risk of breast cancer, as well as the potential interaction of diet (soy and green tea intake) with the exposures of interest among women only (Aims 2 and 3). Dietary intake was assessed at baseline (1993-1998) by in-person interviews using a validated 165-item food frequency questionnaire. HbA1c levels were measured from blood samples collected in the follow-up period after baseline enrollment (1999-2004), and self-reported diabetes diagnosis was determined at the follow-up interview. Self-reported weights at the baseline and follow-up interviews were used to determine weight change. Multivariable linear regression (Aim 1) and proportional hazards regression models (Aims 2 and 3) were used to evaluate these associations. In Aim 1, adjusted mean HbA1c levels were inversely related to soy protein intake (p-value = 0.02; p for trend across the four quartiles of soy protein intake = 0.05) among women; the mean HbA1c difference between the highest and lowest quartile of soy protein intake of 0.07%. We also observed higher HbA1c levels for women with higher green tea intake (p for trend of 0.11), which was in the direction opposite to that hypothesized. In Aim 2, we observed a non-statistically significant increase in breast cancer risk among women with type II diabetes (adjusted hazard ratio [HR]=1.24, 95% confidence interval [CI]: 0.82, 1.86). The assessment of the joint effects of diabetes and lower soy isoflavone intake suggested a weak non-significant interaction between these variables on breast cancer risk; the HR for breast cancer was slightly elevated among those with lower soy isoflavone intake, while among those with higher isoflavone intake the HR was consistent with a null association. There was no evidence of interaction when evaluating soy food, soy protein and green tea intake on the diabetes and breast cancer association. In Aim 3, we did not observe evidence of an increase in breast cancer risk among women reporting weight gain between baseline and follow-up interviews; however, we observed an increase in risk among women who lost between 3 and 5 kilograms between baseline and follow-up interviews (HR=1.31, 95% CI: 0.94, 1.83), which was in the direction opposite of what was hypothesized. This result was similar when we removed breast cancer cases diagnosed within the first two years of follow-up. There was no evidence of interaction between weight change and soy and green tea intake. In conclusion, we provide suggestive evidence that soy protein intake is associated with decreased HbA1c levels among self-reported nondiabetic women. Furthermore, our results suggest that soy isoflavone intake may weakly modify the association between type II diabetes and breast cancer risk. Collectively, the results of these three studies indicate that soy intake may be protective for the development and progression of type II diabetes and could also attenuate the adverse impact of type II diabetes on breast cancer risk. However, given that these results are suggestive for different soy components and the short follow-up time of the prospective evaluation of breast cancer risk, further research is needed to investigate this question. Furthermore, research among populations with varying levels of soy intake is also needed to assess these associations.